2021
DOI: 10.1186/s12882-021-02290-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of semiquantitative point of care urine albumin to creatinine ratio and urine dipstick analysis in a primary care resource limited setting in South Africa

Abstract: Background The prevalence of chronic kidney disease (CKD) is predicted to rise over the next few decades. In resource-limited settings access to central laboratory services is limited. Point-of-care (POC) urine dipstick testing offers the potential to detect markers of kidney damage (albuminuria) as well as markers of other disease processes. We evaluated the diagnostic accuracy of the semi-quantitative albumin-creatinine ratio (ACR) Sysmex UC-1000 POC urine dipstick system as well as the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Our study showed that the sensitivity of semiquantitative ACR to detect albuminuria was higher than specificity, and the NPV was higher than PPV. This was in keeping with other previous studies in that PPV ranged from 46% to 82%, while NPV was higher than PPV ranging from 71% to 99% in all studies 24–31. These findings suggest that a negative result measured by the POCT urinalysis device would be useful for excluding albuminuria, but any positive result would need to be confirmed with a quantitative ACR test.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that the sensitivity of semiquantitative ACR to detect albuminuria was higher than specificity, and the NPV was higher than PPV. This was in keeping with other previous studies in that PPV ranged from 46% to 82%, while NPV was higher than PPV ranging from 71% to 99% in all studies 24–31. These findings suggest that a negative result measured by the POCT urinalysis device would be useful for excluding albuminuria, but any positive result would need to be confirmed with a quantitative ACR test.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 128 female patients (51.4%) and 121 male patients (48.6%) were included. This analysis, stratified for age and sex, represents a novelty with respect to previous studies [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for the first time, to the best of our knowledge, we present a deep and accurate analysis of the results, having performed a sub-stratification based on age (including pediatric subjects) and sex of the enrolled individuals for each parameter. [ 23 ]. In the literature, numerous large-scale studies have tried to set up new protocols for the laboratory diagnosis of albuminuria, creatinuria, and ACR, according to the necessity of a new, faster, and less expensive method useful for large-scale screening of the general population [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amplification methods used in schistosomiasis diagnostics do not limit only to Sh-RPA, at present, they are under extensive research with promising results [18]. Furthermore, schistosomiasis remains a possible cause of isolated haematuria in its endemic regions [19].…”
Section: Discussionmentioning
confidence: 99%